High resolution multiple scenario simulations of future extreme sea levels in hong kong and socioeconomic risks - Zhang Chen; Sicheng Jiang; Xindan Liang; Hongsheng Zhang (Scientific Reports)
Abstract Extreme sea levels (ESLs) induce significant risks to Hong Kong. With climate change, the risks will be amplified, while existing studies have not provided fine-grained simulations of Hong Kong’s future ESL exposure and its socio-economic risks. Employing a GIS-based coastal flood inundation model, this research integrates a high-resolution Digital Terrain Model (DTM) with datasets of ESL forecasts, demography, economy, infrastructure, and land use to estimate the future ESL risks posed on Hong Kong for 2050 and 2100 under two Representative Concentration Pathways (RCPs): RCP4.5 and RCP8.5. The projections indicate that, under RCP4.5, over 27.66% of the population and 39.52% of the Gross Domestic Product (GDP) will be exposed to ESL after 2050. Under RCP8.5 scenario, the exposed population may surpass 31.21%, with economic exposure estimated at 40.98% of GDP after 2050. Under both RCPs, Hong Kong’s ESL-threatened area may range from 8.23 to 11.41%, exposing over 16.09% of the infrastructure to ESL after 2050. Regions in the northwestern Yuen Long, Tuen Mun River Estuary, Rambler Channel coast, Victoria Harbor coast, Shing Mun River, and Tai Po Waterfront have particularly high ESL risks. The findings highlight the need for resilient infrastructure to counteract the long-term risks ESL poses in Hong Kong.